Empowering Teachers in Implementing the Project to Strengthen Students' Pancasila Profile Using STEAM-based Learning for Optimizing Sustainable Development Goals (SDGs) in Junior High School - Utami, Budi; Indriyanti, Nurma Yunita; Probosari, Riezky Maya; Supurwoko, Supurwoko; Fakhrudin, Isma Aziz; Khasanah, Annisa Nur; Hudha, Muhammad Nur (Masyarakat Berdaya dan Inovasi, 2024)
Teachers play a crucial role in preparing quality human resources. One Junior High School in Sragen has implemented the Kurikulum Merdeka (Merdeka Curriculum). Based on interviews, teachers are still experiencing challenges in developing learning instruments and implementing the Science, Technology, Engineering, Art, and Mathematics (STEAM) model and the Project to Strengthen Students' Pancasila Profile. This community service team, Research Group Innovation in Science Classroom (ISC) provided training for teachers on the implementation of STEAM in the Merdeka Curriculum. The training included planning, implementation, mentoring, evaluation, and reporting. This Community Service Program has improved teachers' skills in implementing the Merdeka Curriculum and supporting the Sustainable Development Goals.